MANAJEMEN STRES KERJA PADA PEGAWAI SEKTOR PUBLIK; STRATEGI DAN IMPLEMENTASINYA DI KABUPATEN KOLAKA - Dewi Sulfa Saguni; Muhammad Hidayat Djabbari; Fetni; Widyawati (Journal Publicuho, 2025)
This study aims to explore the levels of work-related stress, its contributing factors, as well as stress management strategies and practices among public sector employees in Kolaka Regency, Southeast Sulawesi. The study employs a mixed-methods approach, combining quantitative data from 92 survey respondents with qualitative data from 12 informants obtained through in-depth interviews and document analysis. Quantitative analysis indicates that 24% of employees experience high levels of stress, with emotional and physical symptoms being the most prominent. Simple linear regression analysis confirms that workload, role ambiguity, and social support are the main predictors of work-related stress. Qualitative findings reveal that the stress management strategies implemented are still partial, informal, and heavily dependent on the initiative of unit leaders, without formal regulations, dedicated budgets, or specialised units. Moreover, social stigma regarding stress management and a lack of a work culture that supports mental health are major barriers to implementation. This study emphasises the need for strategic interventions, including structured institutional policies, technical regulations, stress management training, enhanced social support, and gender-responsive approaches to improve employee well-being and public service quality. The findings contribute to strengthening public sector human resource management systems through more professional and sustainable work-related stress management.